O que pode um performer? revisão crítica dos estatutos musicais para uma prática de experimentação - João Pedro de Queiroz Morales (2023)
This dissertation proposes three revisions of statutes that circumvent Western musical performance in order to lead the performer into a practice of experimentation. Statutes are ideals, conceptions, and concepts that function as a normative referential framework that conditions artistic praxis. For this work, we will focus on the statutes of musical work, score, and performer, addressing some fundamental characteristics and pointing to an expansion of their limits. After an investigation about the concept of experimentation, axis in which the research is articulated, the first review is supported by authors from the field of music, such as David Davies (2011), Lydia Goehr (1992), Nicholas Cook (2013), Paulo de Assis (2018) and Lucia D'Errico (2018). It is exposed here aspects that concern traditional statutes of performance - such as fidelity to the work, to the text, and performer as "mirror" – and, at the same time, proposals that tension such paradigms are pointed out. The second review has a more transversal character, working on notions from philosophy present mainly in Gilles Deleuze and Félix Guattari's thought, which are useful to discuss musical performance in broader terms. Concepts such as plane of immanence, virtual / actual pair, strata, and body without organs are fundamental to this openness. Finally, the third review is based on the description of two experimental performance projects developed during the research: Noches de Verano Porteño, which has as reference the work Verano Porteño, by Astor Piazzolla; and Méditation, faite à la lecture du traité de nomadologie, a performance proposal by Artur Miranda Azzi. It is intended to contribute to studies in musical performance, aggregating transversal works that are based on critical premises about the role of the performer and the conditions surrounding his activity.